A study of the effect of carbon nanotube/nanoclay binary nanoparticle reinforcement on glass fibre/epoxy composites. (2020) - Sen, Bhaskar; Fulmali, Abhinav Omprakash; Gupta K, B.N.V.S. Ganesh; Prusty, Rajesh Kumar; Ray, Bankim Chandra
Abstract: Fiber reinforced polymer composite materials are being used as a potential replacement to metals in a number of applications because of their light weight and superior strength properties. Though FRP composites have found utility in a variety of fields, couple of limitations exists which compels the researchers to find alternative ways to improve the properties even further. One such way is the use of nanofillers like CNT and nanoclay. Different nanofillers have different interactions as a result they affect several properties of composites in various forms. This study aims at investigating the effect of incorporating binary nanoparticles and the variation of composition of nanoclay on mechanical properties of carbon nanotube/nanoclay binary particle reinforced glass fibre/epoxy composite laminates. Composite laminates with different composition with respect to nanoclay has been fabricated i.e. 0.1 CNT- 0.1 NC-GE, 0.1 CNT-0.5 NC-GE, 0.1 CNT-1 NC-GE and their mechanical properties are evaluated. They are further compared to neat GE, 0.1 CNT-GE and 0.5 NC-GE composite samples. Flexural testing showed that variation of composition of nanoclay resulted in a wide variation in properties. 0.1 CNT-0.5 NC-GE showed maximum increase in flexural property with ∼17.9% increase in the flexural strength as well as ∼12.3% increase in the flexural modulus in comparison to neat GE composite. 0.1 CNT-0.1 NC-GE and 0.1 CNT-1 NC-GE did not show appreciable improvement in flexural properties. Upon fracture, fractography study has been done to establish the primary failure mode, extent of bonding and the effect of binary nanofillers on the fracture mechanism using FESEM.